(untitled) (Social Science Review, 2023)
Introduced by the development organizations, in the early nineties of the twentieth century, the concept of good governance emerged as a powerful tool of government management. The term Disaster Management has also been introduced in Bangladesh in the contemporary period. However, Bangladesh is observing the lack of good governance being an obstacle to disaster management. Without ensuring good governance the rise of the death toll due to natural as well as human-induced disasters such as floods, cyclones, river erosion, drought, fire incidents, launch accidents, or building collapse could not be prevented. This study has particularly focused on revealing the relation of landslides to the eight significant characteristics of good governance. The researchers have collected both the primary and the secondary data and have adopted a qualitative method for analysing the data retrieved from Chattogram metropolitan area (previously known as Chittagong) during the research. This study has tried to establish the argument that, lack of the characteristics of good governance including transparency, accountability, rules of law, participation, responsiveness, consensus, inclusiveness, efficiency, and effectiveness is responsible for occurring disasters like landslides. Thus, this study is expected to open a new edge in academic and development research. This will also help the policymakers cope with the guidelines to create necessary policies. Social Science Review, Vol. 39(1), June 2022 Page 35-55